A social accountable model for Iranian dentistry sciences education system: a qualitative study - Imani, Mohammad Moslem; Nouri, Prichehr; Jalali, Amir; Dinmohammadi, Mohammadreza; Rezaei, Farzad (Frontiers in Education, 2023)
Introduction: Social accountability is a new paradigm in dental education and a sort of cultural change. The present study is an attempt to elaborate on the process of social accountability in Iranian dentistry education system. Materials and Methods: The study was carried out as a qualitative work based on grounded theory approach. The participants were selected through purposive sampling and took part in deep semi-structured interviews and data saturation was achieved with fourteen interviews. The main interviews were private and face-to-face interview held in different occasions (morning and afternoon) in a quiet and decent environment. The interviews were held by the author and voice recorded with the permission of the interviewees. Data analyses were done through Strauss Corbin’s method and along with the interviews. Results: The results indicated that the process of social accountability featured three stages of antecedents, mechanisms, and outcomes consisting 619 codes, 16 subcategories, and seven categories. Updating the curriculum, qualified students, appropriate educational environment, appropriate educational technology, monitoring and feedback throughout educational activities, proper interaction with society, and accountably to societies’ needs were the main categories in the study. The concept of proper interaction with society was the core variable. Conclusion: The results indicated that the process of social accountability has major and effective requirements in antecedents, mechanisms, and outcomes stages and it has a good performance in fulfilling the current needs of the society for dentistry services. Still, to cover potential needs, it needs special attention and programming.